Effect of Wine Style and Winemaking Technology on Resveratrol Levels in Wines - Sun,Baoshan (2003)
Resveratrol (3,5,4’-trihydroxystilbene) is a stilbenic phytoalexin produced by grapevines in response to fungal infection or abiotic stress. Much interest has focused, during the last ten years, on its potent antioxidant activities, which may be associated with health benefit for moderate wine consumers. In this work, a method for analysis of trans- and cis-resveratrol of wines by HPLC was developed. Using this method, cis- and trans-resveratrol concentration in different styles of wines (white, rosé and red wines) from several regions of Portugal was determined, and the effects of different winemaking technologies (carbonic maceration, skin fermentation with stem and skin fermentation without stem) on the resveratrol content in wines made from single variety Castelão (Vitis vinifera L.) were studied. The developed method appeared specific, practical, sensitive and selective. Red wines present the highest trans-and cis-resveratrol concentration, followed by rosé wines, while the white wines present the lowest amount of the two isomers, indicating that the resveratrol concentration is dependent on the wine style, which would be associated essentially with maceration of grape solids. The winemaking technology also affects the resveratrol content in wines. Resveratrol concentrations in the wines made by traditional winemaking technologies (fermentation with stems and fermentation without stems) were significantly higher than those in wines made by carbonic maceration. However, there was no significant difference in resveratrol concentrations between stem-contact wines and non stemcontact wine, suggesting that the stems contribute little resveratrol to wines. In addition, prolonged maceration after alcoholic fermentation did not affect the resveratrol concentrations in wines, suggesting that the extraction of resveratrol was complete during or at the end of alcoholic fermentation.